Free ultrasound examination (ultrasound) with the theme "optimize pregnancy examination to guard a healthy pregnancy." - Sri Wahyuni; Asridawati Akib; Rukinah Rukinah; Rosmiaty Pammu; Ria Wahyuni; Rahmawati Rahmawati; Mirnawati Mirnawati (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2024)
The health of pregnant women is one of the key factors in creating a healthy and quality next generation. To increase awareness and access of pregnant women to health services, especially pregnancy examinations. This activity aims to provide ultrasound services to pregnant women, so that they can monitor fetal development more optimally and detect early the possibility of abnormalities or complications during pregnancy. The implementation of this activity involves medical professionals who are experienced in the field of obstetrics and gynecology. Pregnant women who take part in this activity receive a thorough ultrasound examination, accompanied by consultation related to the results of the examination and education about the importance of health monitoring during pregnancy. The results of this activity show the high enthusiasm and need of the community for pregnancy health services, especially in areas that have limited access to health facilities. This activity is expected to be the first step in efforts to improve the quality of maternal and child health in the future. Community Service activities have been successfully carried out with a significant impact on the participants. The program not only provides pregnant women with wider access to quality pregnancy screenings, but also improves their understanding of the importance of health monitoring during pregnancy.